Evaluation of In-Prison Programming for Incarcerated Women: Addressing Trauma and Prior Victimization, United States, 2017-2020 - Buck Willison, Janeen ([Verlag nicht ermittelbar], 2021)
The Urban Institute, in collaboration with the Correctional Leaders Association (CLA), the National Center on Victims of Crime (NCVC), and the Center for Effective Public Policy (CEPP), and with funding from the National Institute of Justice, conducted a two-tiered, 33-month, exploratory mixed methods study of the policies, programs, and practices used nationwide to address the needs of incarcerated women with prior trauma and victimization experiences and prevent in-custody victimization, aiming to generate actionable information for policymakers, practitioners, and program developers. This is the first single, comprehensive study documenting the extent to which facilities implement trauma-informed and gender-responsive approaches to address women's victimization experiences, whether they offer victim services, the range of services offered, and the prevalence of trauma-informed practices in state-level women's correctional facilities. It establishes foundational knowledge for the field regarding the scope, structure, and composition of these approaches, including their trauma-informed components and use in women's correctional facilities.